Influence of Dissolved Oxygen Level on Chitin–Glucan Complex and Mannans Production by the Yeast Pichia pastoris - Inês Farinha; Sílvia Baptista; Maria A. M. Reis; Filomena Freitas (Life, 2022)
The yeast Pichia pastoris was cultivated under different dissolved oxygen (DO) levels (5, 15, 30 and 50% of the air saturation) to evaluate its impact on the production of the cell-wall polysaccharide chitin–glucan complex (CGC) and mannans. Decreasing the DO level from 50 to 15% had no significant impact on cell growth but substrate conversion into biomass was improved. Under such conditions, a mannans content in the biomass of 22 wt% was reached, while the CGC content in the biomass was improved from 15 to 18 wt%, confirming that the DO level also impacted on P. pastoris cell-wall composition. Overall mannans and CGC volumetric productivity values of 10.69 and 8.67 g/(L. day) were reached, respectively. On the other hand, the polymers’ composition was not significantly affected by decreasing the DO level. These results demonstrated that considerable energy savings can be made in the polysaccharide production process by reducing the DO level during cultivation of P. pastoris by improving the overall polymers’ productivity without altering their composition. This has impact on the polysaccharide production costs, which is of considerable relevance for process scale-up and products’ commercialization.